Perkembangan Kecerdasan Kinestetik Anak Melalui Gerak dan Lagu Pada Anak Kelompok B di RA UMDI TAQWA Parepare - Fitriani Sulva Auliah Fitri; Syarifah Halifah (IAIN Parepare, 2023)
Early childhood is at the Golden Age stage, characterized by significant changes in aspects of development (such as language, art and physical motor skills). So that every child can pass this stage well, it is necessary to strive for appropriate education, including the development of children's musical intelligence and kinesthetic intelligence. One of the lessons that teachers can do is by learning movements and songs. This research aims to determine the influence of children's kinesthetic intelligence through movement and songs on group B children at RA UMDI TAQWA Parepare. The method used is a qualitative approach with descriptive methods for group B children at RA UMDI TAQWA Parepare.